RS and GIS for Identification of Potential Sites for Water Harvesting Structures in Bandal Watershed - Singh, J P; Sekar, I; RAO, K H (Journal of Agricultural Engineering, 2013)
A case study was conducted to identify the suitability of potential sites for groundwater recharge structures inBandal watershed, Uttaranchal, using Remote Sensing (RS) and Geographical Information System (GIS). Sitesfor 8 check dams, 86 groundwater recharge structures (percolation tanks) and 15 farm ponds and check damswere identified covering an area of 449,531 m2, 449,531 m2 and 36,448 m2, respectively.